THE SILK CRISIS IN ITALY AND BUKHARA (World Bulletin of Social Sciences, 2021)
This article provides information about the Italians who came to the Emirate of Bukhara in the middle of the XIX century in Italy in search of a crisis in the silk industry and ways to get rid of it and were imprisoned by Amir Muzaffarkhan, as well as some Italians who came to Central Asia in search of a better life
Keywords: Silk; trade route; economic relations; Italians